2006
DOI: 10.1080/07420520601057981
|View full text |Cite
|
Sign up to set email alerts
|

Sleepiness and Sleep in a Simulated “Six Hours On/Six Hours Off” Sea Watch System

Abstract: Ships are operated around the clock using rapidly rotating shift schedules called sea watch systems. Sea watch systems may cause fatigue, in the same way as other irregular working time arrangements. The present study investigated subjective sleepiness and sleep duration in connection with a 6 h on/6 h off duty system. The study was performed in a bridge simulator, very similar to those found on ships. Twelve officers divided into two groups participated in the study that lasted 66 h. Half of the subjects star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 13 publications
2
30
1
Order By: Relevance
“…The studies examined in this review employed a range of schedules, which can be broadly divided into: (i) work/rest schedules, such as 4 hours-on/8 hours-off, 6 hours-on/6 hours-off and 8 hours-on/8 hours-off sched- The last seven days at sea were used in the analyses 6h-on/6-off : TST was similar for both watch rotations 4h-on/8h-off: TST was higher for team one followed by team three then team two watch rotations TST was shorter, frequency of nodding while on duty and excessive daytime sleepiness was higher on 6h-on/6-off compared to 4h-on/8h-off watch systems (24); and (iii) work/ rest schedules that incorporate a swing shift, "dog" shift, layover or disruption, typically in the middle of a roster schedule (22,23,29,33,37). Five studies examined 8 hours-on/8 hours-off roster schedules, all of which were conducted with Australian train drivers (22,25,29,36,37), five examined 6 hours-on/6 hours-off shift schedules, predominantly in ship bridge officers and offshore fleet workers (17,23,30,34,39), and nine examined 4 hours-on/8 hours-off shift schedules all among maritime watch keepers (17, 26-28, 30-33, 35).…”
Section: Schedules and Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies examined in this review employed a range of schedules, which can be broadly divided into: (i) work/rest schedules, such as 4 hours-on/8 hours-off, 6 hours-on/6 hours-off and 8 hours-on/8 hours-off sched- The last seven days at sea were used in the analyses 6h-on/6-off : TST was similar for both watch rotations 4h-on/8h-off: TST was higher for team one followed by team three then team two watch rotations TST was shorter, frequency of nodding while on duty and excessive daytime sleepiness was higher on 6h-on/6-off compared to 4h-on/8h-off watch systems (24); and (iii) work/ rest schedules that incorporate a swing shift, "dog" shift, layover or disruption, typically in the middle of a roster schedule (22,23,29,33,37). Five studies examined 8 hours-on/8 hours-off roster schedules, all of which were conducted with Australian train drivers (22,25,29,36,37), five examined 6 hours-on/6 hours-off shift schedules, predominantly in ship bridge officers and offshore fleet workers (17,23,30,34,39), and nine examined 4 hours-on/8 hours-off shift schedules all among maritime watch keepers (17, 26-28, 30-33, 35).…”
Section: Schedules and Participantsmentioning
confidence: 99%
“…Eight of the studies identified in this review used a within-subject's design (18,22,23,25,29,(36)(37)(38), ten a between-subject's design (17,24,26,27,30,31,34,35,39,40), and four employed a mixed within-and between-subjects design (19,28,32,33). Seventeen studies were field-based (17-19, 22, 24-32, 34-37) and five used laboratory simulations (23,33,(38)(39)(40).…”
Section: Schedules and Participantsmentioning
confidence: 99%
See 3 more Smart Citations